UCL GO: um estudo qualitativo de uma plataforma gamificada adotada como prática em disciplinas do ensino superior - Quiroz, Victor Bruno Alexander Rosetti de (2019)
This work aims to assess the efficiency and impact of the UCL GO gamification tool applied to higher education. The research has two primary areas, games in education and gamification. Among the several references of this work we can highlight the main ones like Huizinga (2000), Fadel et al (2014), Pinheiro and Zaggia (2017). This work is a qualitative study with practical and participative activities, developed during a show of academic works. Through this methodology it was possible to conclude that the UCL GO gamification system is effective and can generate a great impact in higher education, it was also possible to define improvements for the system. I finish this work with a gamification system that allows higher education institutions to implement a more pleasant learning dynamic to students through UCL GO. The system used tools such as Django, Python language, Unity 3D graphics engine and C # language for its development